The Making of Employee Ambassadorship in the Public Sector: Quantitative Study on Individual and Organizational Drivers - De Paolis,Giulia (2025)
This thesis explores the phenomenon of employee ambassadorship in the public sector within the framework of internal branding. The aim is to identify the factors that facilitate or hinder employee ambassadorship, particularly on an individual and organizational level. The study challenged the dominant managerial perspective on internal branding by establishing an employee-centered approach which recognized the active role of employees in internal brand management. The research is grounded on the theory of planned behavior and a quantitative methodology is applied. The 222 data units were collected through an online survey distributed to public sector employees via a snowball sampling approach. A multiple regression analysis was performed to assess the relationships among the variables. The results showed that organizational identification, perceived organizational support and perceived organizational prestige have a positive influence on employee ambassadorship in the public sector, with organizational identification being the strongest predictor. On the other hand, public service motivation and perceived supervisor support did not emerge as significant predictors of employee ambassadorship. Conversely to the other factors, perceived supervisor support holds a negative relationship with ambassadorship, suggesting a hindering effect. The study provides theoretical and practical contributions by advancing the understanding of employee ambassadorship in the public sector.
Keywords: Internal Branding; Employee Ambassadorship; Public Sector; Organizational Identification; Public Service Motivation.